2019
DOI: 10.48084/etasr.2427
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Ramp Geometry on the Flow Characteristics Around Under Pressure Tunnel Aerator Using OpenFoam Open Source Software

Abstract: The flow around the ramp embedded in a pressurized tunnel is divided into various zones downstream of the ramp, including the cavity and the main zone of flow above the shear layer. Ramp angle and height are parameters that affect the flow characteristics such as cavity length, velocity, and pressure coefficient immediately downstream of the ramp. In this study, OpenFOAM open source software and RNG K-ε turbulence model were used to simulate the flow around the under pressure tunnel ramp. In order to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The length and angle of the ramp play an important role in the performance of the hydraulic obstacles. These results were well agreed with the study of Manafpour and Ebrahimnezhadian (2019) where they used CFD methods in order to simulate the air flow around a ramp in a pressurized tunnel and their results showed that inclination angle of ramp was the most influential element that affects the flow more than the ramp height. This study contributes to a variety of engineering fields such as cars designs and some hydrokinetic turbines.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The length and angle of the ramp play an important role in the performance of the hydraulic obstacles. These results were well agreed with the study of Manafpour and Ebrahimnezhadian (2019) where they used CFD methods in order to simulate the air flow around a ramp in a pressurized tunnel and their results showed that inclination angle of ramp was the most influential element that affects the flow more than the ramp height. This study contributes to a variety of engineering fields such as cars designs and some hydrokinetic turbines.…”
Section: Resultssupporting
confidence: 87%
“…This study contributes to a variety of engineering fields such as cars designs and some hydrokinetic turbines. In addition, CFD techniques have proven their efficiency in simulating the flow and representing it very close to reality (Memon et al, 2012;Yuanyuan et al, 2012;Schleicher et al, 2013;Manafpour and Ebrahimnezhadian, 2019;Tokyay and Kurt, 2019;Lopez Mejia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%